Tinjauan Yuridis Penerapan Sanksi Pidana Penjara Dan Pelatihan Kerja Terhadap Anak Pelaku Tindak Pidana Pencabulan (Studi Putusan Nomor: 78/PID.SUS-ANAK/2019/PN. LBP)”. - Syarifuddin Syarifuddin (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
The purpose of the juvenile criminal justice system is basically to protect the dignity of children, especially the protection of the law in the justice system. Therefore, the juvenile justice system is not only emphasized on imposing sanctions on imprisonment alone, but also on children's responsibilities. The research is descriptive in nature because it only explains about legal arrangements, the application of criminal sanctions, as well as the legal considerations of judges in deciding cases of perpetrators of sexual abuse in the Decision of the Lubuk Pakam Court Number: 78 / Pid.Sus-children / 2019 / PN-Lbp).The application of sanctions which is found in legal arrangements contained in Article 71 to Article 83 of the SPPA Law is imprisonment for 3 (three) years 6 (six) months and job training for 2 (two) months. Judge's legal considerations are based on the age of the child and the potential of the child as the next generation who have knowledge and skills, so it is necessary to be equipped with certain knowledge or skills or expertise in the hope that the child returns to the community based on the judge’s believe. The sustained socialization against law enforcement officers and the public need to do, thereby it can optimize joint commitment in handling children dealing with the law.Keywords: Application of Sanctions, Imprisonment and Training, Child Perpetrators, Sexual Abuse.